Anakinra in the Treatment of Patients with Refractory Scleritis: A Pilot Study. (18th August 2018) - Bottin, C.; Fel, A.; Butel, N.; Domont, F.; Remond, A. L.; Savey, L.; Touitou, V.; Alexandra, J. F.; LeHoang, P.; Cacoub, P.; Bodaghi, B.; Saadoun, D.
ABSTRACT: Purpose : This study aimed to evaluate the safety and efficacy of anakinra for severe and refractory scleritis. Methods : Ten patients with severe (i.e. at least 2 ocular relapses per year despite treatment) and refractory [i.e. at least to one disease modifying antirheumatic drugs (DMARDS)] scleritis were treated with anakinra (100 mg/day subcutaneously). Scleritis was associated with inflammatory systemic diseases in 60% of cases. The remission rate defined the primary outcome. Results : Ninety percent of patients were complete responders with a mean follow-up of 19.4 months after starting anakinra. The corticosteroids daily dose decreased from 18.3 ± 4.1 mg to 4.2 ± 4.9 mg, (p < 0.05), at initiation of anakinra and at end of follow-up, respectively. Associated immunosuppressants were stopped in all cases except one. Side effects were observed in 4 patients who did not need anakinra withdrawal. Conclusions : This pilot study suggests the efficacy of anakinra in patients with refractory scleritis.